Peran Mahasiswa Kuliah Praktek Dan Pengabdian Kepada Masyarakat (KPPM) di Desa Sipahutar Kec. Sipoholon - Roni Ulina Sitio; Yayuk Erawati Siahaan; Novita Elisabeth Pakpahan; Hermanto Siahaan; Robinhot Sihombing (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Practical Lectures and Community Service (KPPM) is a form of student service required by IAKN Tarutung, which is carried out in semester VI and lasts for three months. This program aims to improve community welfare and make the nation's life smarter through social activities that use science and technology. In Sipahutar Village, Sipoholon District, KPPM activities are carried out with the aim of increasing children's learning motivation through private tutoring programs, encouraging a spirit of mutual cooperation with the community, and holding healthy exercise with PKK mothers. The research method used involved two main stages: initial observation to identify educational problems in schools, and implementation of a free private tutoring program every Friday for 120 minutes for elementary school children. Apart from that, mutual cooperation activities and healthy exercise with PKK mothers were carried out as part of efforts to improve community welfare and health.The results of KPPM activities show that private tutoring has succeeded in increasing children's interest and motivation in learning in Sipahutar Village. An interactive learning approach adapted to school subjects helps children understand the material more easily. Mutual cooperation carried out with the community shows an increase in togetherness and citizen participation in social activities. Meanwhile, regularly held healthy exercise improves the fitness and health of PKK women, as well as strengthening social relations between them. The conclusion of this activity emphasizes the important role of students in serving society through education, health and other social activities. The KPPM program in Sipahutar Village has succeeded in creating positive change by involving all levels of society in a joint effort to improve welfare and education.